Influence of information sharing behavior on trust in collaborative logistics - Daudi, Morice; Hauge, Jannicke; Thoben, Klaus-Dieter (Springer International Publishing, 2024)
Paper published by Springer International Publishing from the Conference of Collaboration in a Data-Rich World: 18th IFIP WG 5.5 Working Conference on Virtual Enterprises, PRO-VE 2017, Vicenza, Italy, September 18-20, 2017, Proceedings 18 pp. 493–506,